Effect of an auxiliary device on scanning accuracy for multiple implants: an in vitro comparative study - Mingyue Lyu; Dingyi Xu; Yizhou Li; Shiwen Zhang; Heling Zhao; Quan Yuan (Head & Face Medicine)
Abstract Objectives To determine the influence of a consumable auxiliary device, the O-I buckle, on the accuracy of intraoral scanning among complete arches. Methods A standard mandibular model with six implants was used as the master model and was scanned by a precise dental laboratory scanner to establish a reference. Three impression techniques were compared: the conventional splinted open-tray impression (CI group), the digital intraoral scanning technique (IOS group), and IOS with the auxiliary device (OI group). For OI group, six prefabricated O-I buckles were attached for each intraoral scan body (ISB) and the definite models were scanned 10 times. The STL datasets were imported into a 3D inspection software to obtain the trueness and precision values for three scanning ranges (BCDE, BCDEF, and ABCDEF). The trueness was the absolute value of the root mean square (RMS) between the reference and test models, while precision referred to the value of the test group subtracted from each other. The data were statistically analyzed using two-way ANOVA and post hoc multiple comparison tests. Results The impression method (p <.001) and scanning range (p <.001) significantly influenced the trueness and precision of implant impressions for complete edentulous arches. The IOS with O-I buckle showed higher trueness compared to the IOS group for all implant configurations with most being significantly different (p =.758, = 0.04, and = < 0.001 for BCDE, BCDEF, and ABCDEF, respectively) and significantly higher precision was seen in group ABCDEF (p <.001). For four and five implants (group BCDE and BCDEF), there was no significant difference comparing IOS with O-I buckle and CI (p >.05). As the range expanded, the trueness and precision of IOS and OI decreased (p <.05), whereas the accuracy of CI remained stable. Conclusions The auxiliary O-I buckle fixed to the ISBs significantly improved the multiple-implant intraoral scanning accuracy for digital impressions in complete arches; With CI as a reference, the accuracy of IOS with OI buckles were comparable for four and five implants. Clinical relevance The digitization accuracy of intraoral scanning for complete edentulous arches can be improved through IOS with OI buckles. This may lead to improved passive fit of the restoration, improving patient outcomes in a convenient and cheap way.